A new approach for workflow evolution using MDA technology. (15th January 2020) - Abdelkader, Berraouna; Abdelkrim, Amirat; Djamel, Meslati
Most companies, independently of their sizes and activities types, do not provide sufficient adaptability and evolution of their workflow needed to deal with changes in business agreements and organisation methods. In this paper, we treat the adaptability and evolution of workflow based on MDA technology. And we present our new approach for workflow evolution at the design-time, in this approach, the workflow model is described by a specification at a very high level of abstraction using meta-model concepts. The workflow model can be evolved by the workflow designer using model evolution operations. The evolution of models can be managed in different ways. The designers can refine the workflow model according to the evolution scenario proposed by the company manager. In this work, we have developed endogenous rules in ATL which allow the transformation and evolution of workflow model, and among these rules, we have used the endogenous transformation model that affects models expressed in the same language.